Media linktree sebagai media alternatif pembelajaran metamorfosis berbasis learning by doing - Nurullaika, Nurullaika (Maliki Interdisciplinary Journal, 2023)
Technological advances in education force a teacher to master technology in order to bring more creative and innovative learning into line with the demands of technology and curriculum. In developing creative and innovative learning, one important element that cannot be separated is the learning media. The teaching delivered by the teacher will be easily absorbed by students because it uses interesting and concrete media. The old ways of learning must be quickly changed using technology-based learning methods and models. To support student activity in learning, it is important to introduce alternative learning media based on technology that are simple and easy for students to apply. This study aims to prove that link-tree media can be an alternative learning medium for metamorphosis based on learning by doing. The method in this study uses the method of literature review as well as data from the creation of link media created by the researchers.